1856-1857 N.C. Sess. Laws 34 - (:unkn) unknown (My University, 1856)
Pub. Laws, ch. 34, § 23, pt. 4: On every pistol, except such as are used exclusively for mustering, and on every bowie-knife, one dollar and twenty five cents; on dirks and swordcanes, sixty five cents: Provided, however, That of said arms, only such shall be taxable, as at some time within the year have been used, worn or carried about the person of the owner, or of some other, by his consent.
Keywords: TAX - PROPERTY OR SALES